2014
DOI: 10.1007/s40520-014-0223-1
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive ventilation for very old patients with limitations to respiratory care in half-open geriatric ward: experience on a consecutive cohort of patients

Abstract: Very old DNI patients with ARF could be treated with NIV in half-open geriatric ward with trained physicians and nurses. The presence of family members may improve patients' comfort and reduce anxiety level even at the end of life. Further studies are needed to address the effective role of NIV in very old patients with DNI decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…When NIV is applied in a geriatric ward by experienced physicians, and if patients were closely assisted by family members and nurses, the mortality was approximately 25%. 2 In conclusion, the specialized respiratory care setting is a more appropriate setting for the DNI patient than the ICU. 16 This position is supported by a recent Italian study in which the authors reported a NIV success rate of 62% among DNI patients despite their poorer clinical condition.…”
Section: Dni Context and Palliative Carementioning
confidence: 95%
See 4 more Smart Citations
“…When NIV is applied in a geriatric ward by experienced physicians, and if patients were closely assisted by family members and nurses, the mortality was approximately 25%. 2 In conclusion, the specialized respiratory care setting is a more appropriate setting for the DNI patient than the ICU. 16 This position is supported by a recent Italian study in which the authors reported a NIV success rate of 62% among DNI patients despite their poorer clinical condition.…”
Section: Dni Context and Palliative Carementioning
confidence: 95%
“…Vargas et al showed that in a cohort of very old patients (age >80 years) with ARF and DNI decision, 12 h of NIV, carried out in a setting of a half-open geriatric ward with close nursing and family support, ameliorated respiratory function, which allowed the discharge of 75% of patients. 2 In-hospital mortality was related to the admission diagnosis, and was high in very old DNI patients with hypoxemic respiratory failure or end-stage cancer. 14 Previous clinical trials on NIV for very old patients with ARF were carried out all in ICU, respiratory ICU or subintensive care unit by intensive care physicians and included patients with the median age of 75 years.…”
Section: Dni Context and Palliative Carementioning
confidence: 96%
See 3 more Smart Citations